Unsuccessful Xhosa Male Customary Initiation: The Perceptions of Traditionally Circumcised Xhosa Men - Mcata, Mantanzi (Department of Psychology, 2024)
Customary male initiation is a significant rite of passage among the Xhosa people of Southern Africa. It comprises of the surgical removal of the prepuce and other customary practices intended to transition boys into manhood. Though a valued practice among AmaXhosa, various negligent practices in contemporary initiation schools have resulted in high initiate mortality rates and botched circumcisions, resulting in negative perceptions regarding the practice of ulwaluko. Although little research has been conducted on how people perceive this ordeal, botched circumcision processes are viewed taboo and punishable by Xhosa people, and carry with it negative consequences for the young men whose lives are affected. This study investigated the perceptions and stigmas associated with Xhosa men who failed to complete the initiation process as a result of health concerns or botched processes, from the perspective of men who successfully completed the process. Furthermore, it explored the perceived implications and dangers of the stigmas perpetuated. A qualitative research methodology, employing a phenomenology research design, was used in the study. Twelve Xhosa men who completed customary male initiation in accordance with traditional prescripts were recruited using a purposive sampling method. Semi-structured interviews were conducted telephonically and in-person with the participants, and the data was analysed using an inductive thematic approach. The findings suggest that Xhosa men who fail to successfully complete initiation do not uphold hegemonic cultural standards of Xhosa masculinity. These men are subjected to several demeaning practices, such as being called derogatory names and being barred from significant sociocultural spaces. Given this, it is perceived that these men are challenged with a variety of psychological issues including suicidal ideation, low life satisfaction, low self-esteem, trauma, and weakened sense of pride and dignity. The study shed light on the negative perceptions and poor treatment that Xhosa men who fail to complete initiation are subjected to. Although it was acknowledged by the participants that there are several factors that lead to the failure of initiation, including those that were deemed acceptable, failing initiation was frowned upon and was thought to bring shame to a man's family and generations to come. These men were perceived as inferior, incapable of overcoming adversities in their lives, and lacking confidence and leadership skills. The findings of this study have provided insight in an understudied area of Xhosa male initiation which pertains to the social and psychological implications of failing the custom. Keywords: ulwaluko, masculinity, stigma, perception, Xhosa men, customary male initiation